The Prolific Variation, Body Morphometrics, and Breeding Value of Indonesian Local Etawah Goat Based in East Java - Mudawamah, Mudawamah; Ciptadi, Gatot; Retnaningtyas, Irawati Dinasari (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2021)
A crucial trait of a high economic value of goats is calving to more than one kid (prolificacy potency). The high prolificacy potency (> 1 kid) has a higher income compared to single kids. This study described the potential of Indonesian Local Etawah Goat (ILEG) for prolific trait and the morphometric of body and breeding values in various environments as a basis for selection. It involved smallholder farmers who breed ILEG does from 14 villages in East Java. The research was conducted on a field survey to obtain primary data about the phenotypic superior ILEG goats based on the status of the prolific trait. The study used 520 does with 1347 prolific records obtained. The results showed that the prolificacy values ranged from 2.12-1.42 heads/calving (medium to high category). The variation of prolificacy was 0.53, and the breeding values of the prolificacy trait were 1.48-1.74. The average of body morphometrics was varied with the following details. Chest circumference was 81.06 + 4.63 cm, body length was 76.64 + 4.33 cm, shoulder height was 75.34 + 5.83 cm and ear length were 27.44 + 3.02 cm. This study concluded that the prolific rate was medium to high category. The prolific variation was higher than body morphometry variation, and the prolificacy EBVs of breeding villages divided into four unique pattern boxplots. The prolific trait could be the basis for new considerations in the ILEG breeding program, either through selection or mating.